“Trichoderma harzianum en el control de Rhizoctonia solani y Gaeumannomyces graminis en el cultivo de arroz (Oryza sativa L.), en la zona de Babahoyo” - Chuez Cepeda, Jonathan Marcelo (2018)
VIII. SUMMARY The present experimental work was established in the lands of the CEDEGE Irrigation Project owned by the Faculty of Agricultural Sciences of the Babahoyo Technical University, located at Km 12 of the Babahoyo - Montalvo highway, between the geographic coordinates of 277438.26 UTM. West longitude and 110597.97 UTM south latitude; with a height of 8 m.s.n.m. The zone presents a humid tropical climate, with an average annual temperature of 25.60 ° C; an annual rainfall of 2329.8 mm; relative humidity 82% and 998.2 hours of annual average heliophany. Seeds of rice, variety SFL 11 were used as seed material. The treatments studied were Biological (T. harzianum) in doses of 350 and 500 g / ha; Yoke (Tebuconazole 125 + Carbendazin 125) dose of 1000 and 1250 cc / ha; Sitil (Difconazole + Propiconazole) doses of 400 and 500 cc / ha; Carbenex (Carbendazim) dose of 500 and 600 cc / ha and a Control (Without application). The experimental design of Complete Blocks at Random was used with 9 treatments and 4 repetitions. The variables evaluated were subjected to the variance analysis, using the Tukey significance test at 95% probability. All the necessary agricultural work will be carried out in the cultivation of rice for its normal development, such as land preparation, sowing, irrigation, fertilization, weed control, phytosanitary control and harvesting. Based on the results obtained, it was determined that the use of Trichoderma harzianum had no effect on the diseases caused by Rhizoctonia solani and Gaeumannomyces graminis in rice; the highest incidence and severity of the disease was reported in the control treatment, without application of products; The most effective fungicide was Sitil (Difeconazole + Propiconazole) in a dose of 500 cc / ha; the agronomic characteristics such as plant height, panicle length, tillers and panicles / m2 and percentage of full grains obtained a greater response when commercial chemical fungicides were applied and the greater weight of 1000 grains, yield and net profit reached greater value with the use of Sitil (Difconazole + Propiconazole) in a dose of 500 cc / ha with $ 438.09. Key words: Trichoderma harzianum, Rhizoctonia solani, Gaeumannomyces graminis, rice.